All-in-one CISSP exam guide - Maymí, Fernando; Harris, Shon (McGraw Hill-Ascent Audio, 2023)
Thoroughly updated for the latest release of the Certified Information Systems Security Professional exam, this comprehensive resource covers all objectives in the 2021 CISSP exam developed by the International Information Systems Security Certification Consortium (ISC)2®. CISSP All-in-One Exam Guide, Ninth Edition features learning objectives at the beginning of each chapter, exam tips, practice questions, and in-depth explanations. Written by leading experts in information security certification and training, this completely up-to-date self-study system helps you pass the exam with ease and also serves as an essential on-the-job reference. Covers all eight CISSP domains: security and risk management, asset security, security architecture and engineering, communication and network security, identity and access management (IAM), security assessment and testing, security operations, and software development security. Online content includes: 1400+ practice exam questions, graphical question quizzes, a test engine that provides full-length practice exams and customizable quizzes by chapter or exam domain, and access to flash cards.
Online resource; title from title details screen (O'Reilly, viewed May 23, 2023)
Keywords: Computer networks -- Study guides -- Examinations; Telecommunications engineers -- Certification; Réseaux d'ordinateurs; Examens; Guides de l'étudiant; Computer networks; Examinations; Telecommunications engineers; Certification; examination study guides; Audiobooks; Study guides; Livres audio; Guides de l'étudiant